Guardians or Accomplices? Institutional Ownership and Corporate Tax Avoidance: A Meta-Analysis - Ema Aulia Erwanti; Erwin Saraswati; Syaiful Iqbal (Institute of Research and Community Outreach - Petra Christian University, 2026)
Tax avoidance remains widespread, and prior studies report inconsistent results regarding how institutional ownership relates to tax avoidance. To date, no study has employed a meta-analytic approach to examine the nexus between institutional ownership and tax avoidance. This study aims to investigate the effect of institutional ownership on tax avoidance, considering the moderating roles of measurement diversity in tax avoidance and state legal systems. A meta-analytic method was applied to 72 studies from 46 articles (totaling 917,813 observations). This study proves that institutional ownership can effectively limit tax avoidance behavior. However, the diversity of tax avoidance measures and the country's legal system greatly influence its effectiveness. In particular, countries with common law systems are better able to suppress tax avoidance behavior than countries with civil law systems.